Pemberdayaan Masyarakat Melalui Pembentukan Kader Piket Kebersihan Kamar Asrama “PISIKA”di Pondok Pesantren Darul Ihsan Samarinda - Nida Amalia; Azizah Dwi Octavia; Ferry Adiaksyah; Indarmawati Indarmawati; Margita Syavira Risky; Muhammad Youri Jorkaef; Yufita Darusman; Yuliani Yuliani (Jurnal Pesut : Pengabdian untuk Kesejahteraan Umat, 2020)
Community service activities are carried out at the Darul Ihsan Samarinda Islamic Boarding School in Samarinda from November to December 2019 with the target activities of 53 female Dormitory female students. With the theme of Prevention of Skabies and with the title "PISIKA" Room Cleaning Cadres. The purpose of this activity is to create a clean and healthy female hostel environment so as to avoid health problems such as skabies. With the method of forming a voluntary picket cadre that has been chosen to become 3 cadres and given training and direction to run the program in a sustainable manner. The program of community service activities that have been formed is to provide training and direction to cadres to empower their peers regarding the prevention of skabies which in this case relates to room cleanliness which is carried out routinely every day according to the schedule of pickets that have been formed.